Transitions Within the $latex n = 4 $ Complex of Kr VII Obtained Theta-Pinch Light Source - Gomes Trigueiros, Antonio (1986)
The spectrum of six times ionized krypton (Kr VII) has been observed in the 430-1000 Å wavelength range and 23 lines have been identified as transitions between levels of the $latex 4s^{2} $, $latex 4s4d $, $latex 4p^{2} $ and $latex 4s4p $ configurations. For 13 of the lines the classification is new. Revised values are proposed for three levels while for the rest the uncertainty in the existing level values has been considerably decreased. The results are supported by isoelectronic comparisons along the Zn I isoelectronic sequence. The configurations are interpreted by fitting the theoretical energy expressions to the observed energy levels using least-squares techniques. The parameter values are compared with results from Hartree-Fock calculations.